2009
DOI: 10.1017/s1368980009004789
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriis not associated with anaemia in Latin America: results from Argentina, Brazil, Bolivia, Cuba, Mexico and Venezuela

Abstract: Objective: To investigate the association between Helicobacter pylori infection and anaemia. Design: Six cross-sectional studies. H. pylori infection was assessed by the [ 13 C]urea breath test using MS or IR analysis. Hb was measured for all countries. Ferritin and transferrin receptors were measured for Argentina, Bolivia, Mexico, and Venezuela. Setting: Health services in Argentina, Brazil and Mexico or public schools in Bolivia, Cuba and Venezuela. Subjects: In Argentina, 307 children aged 4-17 years refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 61 publications
4
39
2
2
Order By: Relevance
“…The findings of the present study were in agreement with those of Santos et al (2009) that there is no evidence to support the hypothesis that H. pylori contributes to anemia in children, adolescents, adults, or pregnant women in six Latin American countries. Neither did this study which showed no significant relationship between H. pylori and anemia.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of the present study were in agreement with those of Santos et al (2009) that there is no evidence to support the hypothesis that H. pylori contributes to anemia in children, adolescents, adults, or pregnant women in six Latin American countries. Neither did this study which showed no significant relationship between H. pylori and anemia.…”
Section: Discussionsupporting
confidence: 89%
“…South Africa: 87% [16], Egypt: 72% [17]), in Latin America (e.g. Bolivia: 78% [18]) and in some Asian countries (e.g. Pakistani: 92% [19]).…”
Section: Discussionmentioning
confidence: 99%
“…This allowed the exclusion of common causes of iron deficiency such as gastrointestinal bleeding, peptic ulcer disease, extensive erosions and celiac disease. Furthermore, in contrast to other studies [16], [30], female adolescents with heavy menstrual blood loss were not included because menstrual iron loss is an important determinant of iron status in young women. Intestinal parasitic infections that lead to blood loss were also an exclusion criterion.…”
Section: Discussionmentioning
confidence: 99%